Energy and substance transfer in magnetron sputtering systems with liquid-phase target; Vacuum; Vol. 124 - Bleykher (Bleicher) G. A. Galina Alekseevna; Krivobokov V. P. Valery Pavlovich; Yuryeva A. V. Alena Victorovna; Sadykova I. (2016, 2016)
Title screen